The Effect of Administrative Performance on Service Quality at SMA Negeri 2 Parepare - Niswaty, Risma; Hidayat, Andy; Akib, Haedar (Universitas Negeri Makassar, 2022)
Administrative performance, namely all mechanisms that can assist, expedite, increase activity and efficiency of the administrative process by providing all the necessary data and information, so that the administration runs smoothly. This study aims to determine how the effect of administrative performance on service quality in SMA Negeri 2 Parepare. This research uses quantitative methods. Data collection techniques were carried out through observation, questionnaires, interviews, and documentation. The sample used in this study was the entire population, as many as 106 students at SMA Negeri 2 Parepare. The data from the results of this study used the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential statistical analysis. The results of this study indicate that the indicators used in each of these variables indicate where the administrative performance is in the sufficient category. The service quality variable is in the sufficient category. Based on the correlation test, there is a very strong/very high relationship between the two variables. So it can be concluded that there is a significant influence between administrative performance on service quality at SMA Negeri 2 Parepare.